Análisis de la oferta y demanda en el sector de construcción de edificaciones residenciales alrededor de la gestión empresarial en los Grupos de Interés - Hernández-Carrillo, Carlos-Gabriel; Rojas-Sarmiento, Jorge-Andrés; Gonzalez-Sanabria, Juan Sebastian (Revista Científica, 2021)
The global market was immersed in an environment of economic and political uncertainty, where trade and industrial production showed signs of marked weakness. However, in developing countries like Colombia, with a moderate expected economic growth, attributed to the implementation of strategies aimed at creating jobs, building public infrastructure and services to meet the needs of their rapidly expanding and urbanizing populations. Consequently, this research analyzed the external phenomena that have impacted the Colombian economy on the construction sector's housing supply and demand behavior. All the above, through the analysis of economic indicators, public policies, and stakeholder management around the use of tools, approaches, and methodologies established by different standards in project management and the analysis of a business sample located in the city of Tunja. As mentioned above, it allowed the establishment of susceptibility to external economic phenomena and government policies in the construction sector. Those would enable the increased demand and boost other areas of the economy through stakeholders' effect in the supply and business capacities concerning its management, recognizing the expectations in the formulation and elaboration of projects in the current context. Nevertheless, companies related to the construction sector do not have adequate tools and personnel for this integral development, allowing them to identify factors when evaluating stakeholder management's business capacities, contributing to generating new methodologies and instruments that enable increasing construction projects' success.